The 20Ne(d, p)21Ne transfer reaction in relation to the s-process abundances. Issue 1 (January 2016) - Nsangu, C T; Laird, A M; Parikh, A; Adsley, P; Birch, M D; Chen, A A; Faestermann, T; Fox, S P; Fulton, B R; Hertenberger, R; Irvine, D; Kay, B P; et al.
Abstract: A study of the 20 Ne( d, p ) 21 Ne transfer reaction was performed using the Quadrupole Dipole Dipole Dipole (Q3D) magnetic spectrograph in Garching, Germany. The experiment probed excitation energies in 21 Ne ranging from 6.9 MeV to 8.5 MeV. The aim was to investigate the spectroscopic information of 21 Ne within the Gamow window of core helium burning in massive stars. Further information in this region will help reduce the uncertainties on the extrapolation down to Gamow window cross sections of the 17 O( α, γ ) 21 Ne reaction. In low metallicity stars, this reaction has a direct impact on s -process abundances by determining the fate of 16 O as either a neutron poison or a neutron absorber. The experiment used a 22-MeV deuteron beam, with intensities varying from 0.5-1 μ A, and an implanted target of 20 Ne of 7 μ g/cm 2 in 40 μ g/cm 2 carbon foils. Sixteen 21 Ne peaks have been identified in the Ex = 6.9-8.5 MeV range, of which only thirteen peaks correspond to known states. Only the previously-known Ex = 7.960 MeV state was observed within the Gamow window.